The Role of Ecolabeling in Green Marketing: A Consumer Perspective - K, Jayashree. (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
Aims: In this study the in-depth knowledge about how consumers perceive and are aware of the eco-labels in green marketing and how well these labels are effective in nature [1]. Eco-labels can bring out a positive perception in people towards the environment. In this study, a descriptive analysis is conducted by understanding the effectiveness of ecolabelling and we also come across how the dynamics towards eco-labelling has made a difference in the FMCG or fast-moving consumer goods. We also understand how consumer buying behaviour changes towards eco-labelled products. Non-probability sampling and survey were done using a questionnaire. The research took place in Bangalore and the duration to complete this research paper was around 30 days. A mixed methodology is used. Through this study, we understand people’s choices and their perception towards the eco-labels and their awareness about the eco-labels and if given a choice would their preference still be the same or changed. The results obtained, eco-labels play a vital role in green marketing by serving as a trusted guide for environmentally conscious consumers. Through providing transparent information about the sustainability of products, eco-labels empower consumers to make informed choices aligned with their values [2]. Overall, eco-labels represent a valuable tool in promoting sustainability and influencing consumer behaviour towards more environmentally friendly purchasing decisions.